GLOBAL EPIDEMIOLOGY OF VIRAL HEPATITIS: CURRENT SITUATION AND FUTURE PROJECTIONS - Norqulov Sardor Jumaniyozovich (The Conference Hub, 2025)
Viral hepatitis is a widespread and serious global health concern. Hepatitis A, B, C, D, and E viruses can infect humans through various transmission routes, leading to both acute and chronic diseases. According to the World Health Organization (WHO), millions of people worldwide contract hepatitis infections annually, which can result in severe complications such as liver cirrhosis and liver cancer. Among the different types, hepatitis B and C are considered the most dangerous due to their potential to develop into chronic conditions with long-term health consequences.